2007
DOI: 10.1063/1.2718882
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic-pattern formation in anodic aluminum oxide templates

Abstract: Formation of disordered and ordered pore patterns in two dimensions have been reported in pore growth in nanoporous alumina templates. This is explained in terms of instability in the pattern formation. Here, we report our observation of instability in the pattern formation in three dimensions, that is, along the cylindrical axis of the pores. The instability is revealed in the form of dendrites in the pore pattern under certain fabrication conditions. We examine the conditions under which two- and three-dimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…7 In these applications, one usual requirement is that the arrangement of the pore-channels inside the porous alumina should be hexagonally self-ordered, and this means that the growth of the porechannels during aluminum anodization should be a self-ordering process 1, 2 with as infrequent splitting, merging or termination as possible. 8,9 Plenty of previous efforts have been made to find the anodization conditions which can result in self-ordering porous alumina patterns. Masuda and Fukuda found that mild anodization conducted in 0.3 M oxalic acid at 40 V at 0 • C can result in selfordering patterns.…”
Section: Introductionmentioning
confidence: 99%
“…7 In these applications, one usual requirement is that the arrangement of the pore-channels inside the porous alumina should be hexagonally self-ordered, and this means that the growth of the porechannels during aluminum anodization should be a self-ordering process 1, 2 with as infrequent splitting, merging or termination as possible. 8,9 Plenty of previous efforts have been made to find the anodization conditions which can result in self-ordering porous alumina patterns. Masuda and Fukuda found that mild anodization conducted in 0.3 M oxalic acid at 40 V at 0 • C can result in selfordering patterns.…”
Section: Introductionmentioning
confidence: 99%
“…One essential requirement for anodic porous alumina to be used as a template is the arrangement of the nanopore channels should be well ordered [69,93,94], with as infrequent splitting, merging or termination of pore channels as possible [101,175]. Because in disordered anodic porous alumina, plenty of the pore channels are not straight but branched from pore mouth to pore bottom, the deposited materials cannot be easily filled into the channels, during the commonly used methods such as electrochemical deposition, capillary force assisted nanoimprinting, or CVD [28,51,79,123,176], also the obtained nanowire, nanopillars, or nanotubes will not be straight.…”
Section: Mild Anodization and Hard Anodizationmentioning
confidence: 99%
“…However, in structures with disordered in-plane patterns, the straightness of the pore channels is usually not maintained during growth, and on progressing from the top to bottom, the growth of a given pore may fall behind its neighbors or even completely terminated, or the pore can branch to form two or more new ones [95]. As pore merging, termination, or splitting happens, the aspect ratio of the pore channels in disordered structures is usually not larger than 20 [93,101]. A thin scallop-shaped oxide barrier layer exists at the pore bottom which separates the metal substrate from the electrolyte in the pore channels during the anodization.…”
mentioning
confidence: 99%
“…As a result, the aspect ratio of the pore channel, i.e. the channel length to pore diameter, can be greater than 1000 for self-ordered AAO [92,101,102], while the ratio may be less than 20 for disordered AAO [92,103]. Because the in-plane porous patterns are just snap-shots during the growth of the AAO layer, it is the growth stability of pore channels during anodization which determines the self-ordering quality of AAO.…”
mentioning
confidence: 97%